1982
DOI: 10.1161/01.cir.65.5.846
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the acute and long-term hemodynamic effects of ventricular inhibited and atrial synchronous ventricular inhibited pacing.

Abstract: SUMMARY Sixteen patients treated with a noninvasively programmable pacemaker were examiined after a prolonged period of ventricular inhibited (VVI) and atrial synchronous ventricular inhibited (VDD) pacing. Maximal working, capacity was determined by bicycle ergometry. Atrial and ventricular rates, brachial artery cuff pressure and breathing rate were determined at rest and during exercise. There was a mean increase in working capacity of 24% with VDD compared with VVI pacing (p < 0.001). Thirteen of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
11

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(55 citation statements)
references
References 16 publications
(6 reference statements)
0
44
0
11
Order By: Relevance
“…In addition, the complication rates attributed to the most sophisticated systems have been considered high and of difficult management, particularly for the nonspecialized physician [3][4][5][6] . Several studies have shown the clinical and hemodynamic advantages of the DDD,C mode stimulation as compared with the VVI,C mode, both for total atrioventricular block and sick sinus syndrome 4,6,10,14,15 . The VVI,C pacemaker has been associated with a lower physical capacity 4,15 , a worse quality of life 6,10,15 , an enlargement of the cardiac silhouette 14 , the pacemaker syndrome 16 , and a higher mortality rate 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the complication rates attributed to the most sophisticated systems have been considered high and of difficult management, particularly for the nonspecialized physician [3][4][5][6] . Several studies have shown the clinical and hemodynamic advantages of the DDD,C mode stimulation as compared with the VVI,C mode, both for total atrioventricular block and sick sinus syndrome 4,6,10,14,15 . The VVI,C pacemaker has been associated with a lower physical capacity 4,15 , a worse quality of life 6,10,15 , an enlargement of the cardiac silhouette 14 , the pacemaker syndrome 16 , and a higher mortality rate 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown no significant difference in regard to mortality 3 or functional capacity 5 . Atrioventricular resynchronization, considered responsible for improving physical capacity by some authors 4,14 , was challenged by Chu-Pak Lau et al 18 , who attributed this increment basically to variations in heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Während die hämodynamische Überlegen-heit der vorhofgesteuerten (DDD-/VDD-) gegenüber der festfrequenten Ventrikelstimulation (VVI) im Langzeitverlauf belegt ist (2,6,11,14,15) …”
unclassified
“…) KRUSE & RYDÉN, 1981;KRUSE et al, 1982;PEHRSSON, 1983;PERRINS et al, 1983;KRISTENSSON et al, 1985a;KRISTENSSON et al, 1985b, em estudos clínicos pareados, relataram a melhora da capacidade física dos pacientes, de 13 a 22%, com a mudança da estimulação ventricular para atrioventricular. KARLÖF, 1974;KAPPENBERGER et al, 1982;KRUSE et al, 1982;PEHRSSON & ASTRÖM, 1983e NORDLANDER et al, 1987 As principais desvantagens da estimulação atrioventricular universal são: presença de dois eletrodos intravasculares; maior tempo cirúrgico; menor duração da bateria do gerador de pulsos, devido ao maior consumo de energia e custo (cerca de 40% maior que os sistemas ventriculares). (DODINOT & KUBLER, 1982;KRISTENSSON et al, 1984).…”
Section: XXunclassified
“…(FRANCIOSA et al, 1981;WEINER, 1983;BUGNI 1984;FRANCIOSA, 1984;WEBER et al, 1984a;WEBER et al, 1984b. ) Com o objetivo de estudar comparativamente modos de estimulação cardíaca artificial, o estudo hemodinâmico tem sido empregado isoladamente (SAMET et al, 1966;SAMET et al, 1968;LEINBACH et al, 1969;FANANAPAZIR et al, 1983), ou associado ao exercício (KARLÖF, 1974;KAPPENBERGER et al, 1982;KRUSE et al, 1982;PEHRSSON & ASTRÖM, 1983).…”
Section: (Tabela Vi) Tabela VI -Estudo Comparativo Das Variáveis Hemunclassified